Quality of Regional Government Financial Reports: The Effect of Internal Control, Quality of Human Resources and Implementation of the Accrual Basis - Festus Reymon Kesse; arlan tahir; Ryans Ardiansyah (Faculty of Business and Economics , Universitas Yapis Papua, 2023)
Quality government financial reports will be reflected in the information presented in the financial reports. Therefore, the control factors applied, the quality of the employees, and the accounting system applied will also determine the quality of the financial reports produced. This research aims to examine three factors, namely internal control, quality of human resources, and the application of the accrual basis to the quality of Regional Government financial reports. Sampling in this research used a non-probability sampling design with a judgment sampling technique using an instrument in the form of 90 questionnaires which were distributed directly. The data analysis method in this research used Structural Equation Model (SEM)-PLS analysis. The research results show that the quality of Human Resources and the application of the accrual basis affect the quality of Regional Government financial reports, but internal control is unable to have a significant impact on the quality of Government financial reports.